Pengaruh Penggunaan Laba, Arus Kas, Likuiditas Dan Leverage Untuk Memprediksi Kondisi Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2017-2019 - Yois Nelsari Malau; Rodasnita Purba; Jessica Maranatha Br Saragih; Dewi Sartika Br Sinambela (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study is to determine the effect of Profit, Cash Flow, Liquidity, Leverage on financial distress. The sample is 48 companies, multiplied by 3 years so that the number of observations is 144, the data is taken with documentation and purpose sampling techniques with the results of the 2017-2019 BEI financial statements. And simultaneously it was concluded that Profit, Cash Flow, Liquidity, Leverage had a significant effect on financial distress conditions in manufacturing companies listed on the IDX for the period 2017-2019. Keywords: Profit, Cash Flow, Liquidity, Leverage, and Financial Distres.